Injury prevention considerations in adolescent overhead-throwing athletes - Zaremski, J. L.; Zeppieri, G.; Tripp, B. L (Current Physical Medicine and Rehabilitation Reports, 2019)
The purpose of this manuscript is to summarize concepts to consider when implementing ways to prevent injuries in adolescent overhead-throwing athletes. The goal of this review is to provide an updated and novel overview for the practitioner who cares for this specific patient population. Recent Findings